Well-Posedness for a Fourth-Order Equation of Moore–Gibson–Thompson Type - Lizama-Yanez, C (University of Szeged, 2021)
In this paper, we completely characterize, only in terms of the data, the well-posedness of a fourth order abstract evolution equation arising from the Moore– Gibson–Thomson equation with memory. This characterization is obtained in the scales of vector-valued Lebesgue, Besov and Triebel–Lizorkin function spaces. Our characterization is flexible enough to admit as examples the Laplacian and the fractional Laplacian operators, among others. We also provide a practical and general criteria that allows Lp–Lq-well-posedness. © 2021, University of Szeged. All rights reserved.